Isolated Lateral Release is Inferior to Medial Patellofemoral Ligament Reconstruction for Surgical Management of Patella Instability in Pediatric Patients. Issue 5 (31st May 2022) - Varshneya, Kunal; Money, Adam; Curtis, Daniel; Ray, Taylor; Shea, Kevin; Abrams, Geoffrey D.; Safran, Marc; Sherman, Seth L.
Background: The optimal treatment for chronic patella instability remains controversial. Medial patellofemoral ligament reconstruction (MPFLR) has emerged as the "gold standard" for soft tissue stabilization. However, isolated lateral release (ILR) is still commonly performed to treat chronic patella instability despite growing evidence against this approach. Hypothesis/Purpose: Our purpose is to evaluate long-term revision rates and short-term post-operative complications in pediatric patients undergoing either MPFLR or ILR for recurrent patellar instability. The hypothesis is that MPFLR is a superior treatment option with reduced long term revision rates and comparable short-term complications. Methods: The MarketScan database was queried from 2007-2015 to identify patients who underwent MPFLR or ILR as their primary surgical treatment of their chronic patellar instability. Patients were excluded if they had incomplete records up to 5 years or if they underwent concomitant osteotomy or cartilage restoration during their index stabilization procedure. Baseline demographic data and patient co-morbidities were documented. Two and five year revision surgical stabilization rate and post-operative complications were reported. Results were analyzed statistically. Results: This study identified 471 patients (mean age 15.6 years, female 56.9%) who underwent MPFLR and 528 patients (mean age 15.5 years, female 70.5%) who underwent ILR for chronic patellar instability. Patients were stratified into two mutually exclusive groups: 1) MPFLR only or 2) ILR only. Patients who underwent MPFLR experienced higher rates of overall complications within 90 days of surgery (8.7% vs 4.9%, p = 0.0171). MPFLR had a higher rate of early wound complications (0.8% vs. 0%, p <.033) There was no difference in revision stabilization rate between MPFLR and ILR at 2 year follow-up. However, at 5 years of follow-up, 8.9% of patients who underwent ILR underwent revision surgery compared to 3.0% of patients who underwent MPFLR as their index surgery (p < 0.0001). Conclusions: Isolated lateral release is an inferior treatment option for surgical stabilization of chronic patella instability as compared to medial patellofemoral ligament reconstruction in pediatric patients. Despite slightly higher rate of short term complications in the MPFLR group and similar revision rates at 2 years, MPFLR has significantly decreased risk of revision stabilization at 5 year follow-up. Table 1. Postoperative Complications - within 90 days Table 2. Quality Outcomes